A novel introduction to file I/O using KML and Google Earth - Elizabeth, Vidal (2018)
In this paper, we propose the use of simple KML files to increase student engagement when learning file I/O. We also report on our trial study where we had one group of students learn I/O functions using conventional exercises while we had another working with KML-based files that could trivially be viewed in Google Earth. Our assessment of student engagement indicated that students in the experiment group registered significantly higher in the usefulness and interest dimensions.